HDAC10 and its implications in Sézary syndrome pathogenesis - Pieniawska, Monika; Rassek, Karolina; Skwara, Bogumiła; Żurawek, Magdalena; Ziółkowska-Suchanek, Iwona; Visser, Lydia; Lodewijk, Monique; Sokołowska-Wojdyło, Małgorzata; Olszewska, Berenika; Nowicki, Roman J.; Stein, Tomasz; Dańczak-Pazdrowska, Aleksandra; et al. (Frontiers in Cell and Developmental Biology, 2025)
Cutaneous T-cell lymphomas (CTCL) are a group of rare hematological malignancies characterized by infiltration of malignant T-cells into the skin. Two main types of CTCL constitute of Mycosis Fungoides (MF), a more indolent form of the disease, and Sézary syndrome (SS), the aggressive and leukemic variant with blood involvement. Sézary syndrome presents a significant clinical challenge due to its very aggressive nature, poor prognosis, and treatment resistance, and to date, the disease remains incurable. Histone deacetylase inhibitors have gained attention in CTCL treatment with promising results, but they expose limited specificity and strong side effects. Recent genomic studies underscore the role of epigenetic modifiers in CTCL pathogenesis, prompting an investigation into HDAC10, a member of class IIb HDACs, in SS. HDAC10 was investigated in different cancers, revealing its involvement in cell cycle regulation, apoptosis, and autophagy, but its role in CTCL is unknown. In this study we aimed to determine the role of HDAC10 in SS, focusing on its cellular localization, role in cell growth, and therapeutic potential. We indicated that HDAC10 is overexpressed in SS patients and located mainly in the cytoplasm. Its overexpression leads to an inhibitory effect on apoptosis progression when exposed to the pro-apoptotic compound Camptothecin (CPT). Knockdown of HDAC10 resulted in reduced cell growth and induction of apoptosis and autophagy, highlighting its potential importance in CTCL pathogenesis. Whole transcriptome analysis indicated that HDAC10 is associated with crucial cancer-related pathways, for example, hematopoietic cell lineage, PI3K-Akt signaling pathway, Ras signaling pathway, MAPK signaling pathway or JAK-STAT signaling pathway, which are critical for the survival and proliferation of malignant T cells. Inhibition of HDAC10 with selective HDAC10i increased the sensitivity of Sézary cells to the pro-apoptotic CPT. Our findings demonstrate that HDAC10 plays a key role in the molecular background of Sézary syndrome, highlighting its importance in the cellular mechanisms of the disease.